Associations between olfactory reference disorder and social phobia – results of an internet-based study - Reuter, Julia; Grocholewski, Anja; Steil, Regina (Frontiers in Psychology, 2024)
Despite the similar clinical features of Olfactory Reference Disorder (ORD) and Social Phobia (SP), or studies showing elevated comorbidity of the two disorders, and the conceptualization of ORD as a form of SP in the East Asian culture, to our knowledge, the relationship between ORD and SP has not been investigated. This study examined the association of ORD according to the 11 th revision of the International Classification of Diseases (ICD-11) and SP in 225 German university / college students who completed self-ratings with regard to socio-demographic data and symptoms of SP and ORD within an anonymous internet-based survey. Symptoms of SP were assessed with the Social Phobia Inventory (SPIN). Symptoms of ORD according to the ICD-11 were assessed with the Olfactory Reference Disorder Questionnaire (ORDQ), developed for this study. In our sample, 86.6% of the participants who met the self-rated features for ORD also met the self-rated criteria for current SP. ORD severity scores were significantly related to SP. Participants with and without self-reported ORD differed significantly in their SP total scores. SP severity was also significantly correlated with poorer insight of ORD-related beliefs, greater ORD-related avoidance of intimate relationships and higher levels of shame and fear of rejection due to body odor. These preliminary findings indicate that ORD could be closely related to SP and highlight the need for future research on the relationship of ORD and SP in order to gain a better understanding of the development, maintenance, treatment and classification of ORD.